Online university used book center / Chang Mei Ying - Chang , Mei Ying (2003)
Online university used book center (OUUBC) is a web-based application to provide undergraduate, gradute student and public in Malaysia environment to buy and saearch the university used books online. Next, it enables administrator to coordinate the task and manage the database online. The main objective of OUUBC is to sell and search the university used books in order to increase work efficiency. A thorough research and analysis has been done. The information gathered via the internet, library and the observation of existing website. PHP (web development), MYSQL (database) and Apache (web server) have been chosen as the development tools for OUUBC base on their strength and outstanding advantages compared to other in-market tools. The functional requirement for OUUBC are membership, search function online purchasing and administration features. The most significant feature that makes OUUBC different from other existing product is provide the services using the advanced online technologies. Besides OUUBC eliminates the expansive shipping charge by the existing system via the delivery service by POS Malaysia. Finally, OUUBC is expected to provide a user friendly interface that save the time for users and administrators.